The historical collection of the MG herbary: history, vulnerability and conservation - Sousa da Rocha, Antônio Elielson; Gil, André dos Santos Bragança (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2025)
The herbarium of the Museu Paraense Emílio Goeldi (MG), the oldest in the Amazon, has, among its important collections, a Historical Collection with more than 17 thousand specimens registered in its database (books tumbled), however more than 21% of these records were not found in the computerized data currently in use. Faced with this finding, investigations were carried out in an attempt to understand this significant disappearance of records, and some questions were raised: What happened to these missing records? When did the records disappear? Did the exsiccates also disappear from the collection? Did these specimens belong to a single taxon (family, genus, species)? Was the history of poor conservation of the collection responsible for the disappearance of these records? The results showed that the families Apocynaceae, Asteraceae, Bignoniaceae, Clusiaceae, Euphorbiaceae, Fabaceae, Malpighiaceae, Malvaceae and Orchidaceae would be more strongly indicated as susceptible to insect and fungal attacks.
Keywords: Botanical collection; conservation of specimens; vulnerable taxa.